Magang Kerja: 3D Animator pada PT Kriya Kreatif Anugerah – Moving Things Production - Stephanie Stephanie; Jimmy Pratama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
Animation is the process of creating an audio-visual compositions based on the arrangement of images and time, resulting in a moving illustrations. Animation has become an interesting media because of its increasingly sophisticated technological developments, especially 3D animation. In producing an animation needs a long learning and training technique, and involves many people in the production process. In Indonesia, the animation industries have started to develop, but in terms of Human Resources (HR) is still minimum. Moving Things Production is one of the industries engaged in 3D animation. The establishment of this company is due to an idea that is to develop animation in Batam City and provide more career opportunities to fresh graduate students. Therefore, the aim of this activity is to help partners in developing their 3D animation projects and to get opportunities for students to practice their knowledge in working world in the field of 3D animation. The method used in this activity is the pre-production stage, production stage, and post-production stage. The creation of this 3D animations use Autodesk Maya software. The results of the implementation this activity are 3D animations playblast video that displays the movement of action and acting on 3D character and 3D character image that displays 3D character that are pointing at something.